Análisis del proceso de producción de biodiesel a partir de la borra de café. (2022)
This project intends to make a proposal for the production of biodiesel taking coffee grounds as raw material, analyzing the characteristics of the production process through the use of a bibliographic analysis and an analysis is carried out for the purification of the biodiesel obtained with the use of simulation software Aspen Plus V9, for which different processes are studied and compared. Coffee grounds are one of the main residues generated by the freeze-dried coffee industry, in recent years their use has been investigated for the production of various products, mainly their use as a raw material for the production of biofuels has been studied. Coffee grounds have an approximate lipid content of 14%, therefore, on many occasions, the extraction of its oil is carried out for the production of biodiesel. Through a bibliographic analysis, different processes were found for the transesterification of coffee grounds, among them the in-situ transesterification and the basic homogeneous transesterification with different operating conditions. From the bibliographical analysis of the characteristics of the coffee grounds and its oil, a basic homogeneous transesterification was chosen with a methanol/oil ratio of 6:1 and a NaOH catalyst.